Comparing Provenance Data Models for Scientific Workflows: an Analysis of PROV-Wf and ProvOne - Oliveira, Wellington; Missier, Paolo; de Oliveira, Daniel; Braganholo, Vanessa (Anais do Brazilian e-Science Workshop (BreSci); 2016: Anais do X Brazilian e-Science Workshop, 2016)
Scientific workflows rely on provenance to be understandable, reproducible and trustworthy. Nowadays, there is a growing demand for interoperability between provenance data generated from heterogeneous workflow management systems. To address this issue, some provenance models have been proposed by extending PROV to support specific requirements of scientific workflows. In this paper, we present two prominent provenance models for scientific workflows, PROV-Wf and ProvOne, which are specializations of PROV, and compare their elements and relationships. Our goal is to provide an overview of each one and to support the choice for the most suitable for a specific context.